What Endgame for the Deglobalisation Narrative? - Simon J. Evenett (Intereconomics, 2022)
From the perspective of international economic governance, other than casting aspersions on the judgement of those that negotiated previous multilateral trade accords and the accession of China to the World Trade Organization, the deglobalisation narrative is silent on how to reform that organisation – or what to salvage from existing global trade rules.
Keywords: F13; F23; F52; 330